Semi-passive powered biotelemetry for small animals - Volk, Tobias; Gorbey, Stefan; Lemmer, Björn (Sensors and actuators. A, Physical, 2015)
Mice and rats make up 95% of all animals used in medical research and drug discovery and development. Monitoring of physiological functions such as ECG, blood pressure, and body temperature over the entire period of an experiment is often required. Restraining of the animals in order to obtain this data can cause great inconvenience. The use of telemetric systems solves this problem and provides more reliable results. However, these devices are mostly equipped with batteries, which limit the time of operation or they use passive power supplies, which affects the operating range. The semi-passive telemetric implant being presented is based on RFID technology and overcomes these obstacles. The device is inductively powered using the magnetic field of a common RFID reader device underneath the cage, but is also able to operate for several hours autonomously. Being independent from the battery capacity, it is possible to use the implant over a long period of time or to re-use the device several times in different animals, thus avoiding the disadvantages of existing systems and reducing the costs of purchase and refurbishment.